PTH-157 The Introduction of Biosimilar Infliximab (CT-P13) through A Managed Switching Programme Generates Significant Cost Savings with High Levels of Patient Satisfaction. (17th August 2016) - Rahmany, S; Cotton, S; Garnish, S; McCabe, L; Brown, M; Saich, R; Lloyd, D; Gordon, JN
Abstract : Introduction: Biosimilar infliximab (CT-P5013) has been licensed in the UK for over a year with the potential for significant cost savings, though uptake to-date has been surprisingly slow. We report the introduction of biosimilar infliximab through a closely managed switching programme. Methods: Following the licensing of biosimilar infliximab we made a decision to instigate a closely managed switching programme encompassing all patients on maintenance treatment with Remicade and all new starters. A working party was set up with strong managerial support to deliver the project. We initially estimated savings of £400, 000/year to the local health economy. Following meetings with the 3 local CCGs agreement was confirmed for a 50:50 gain share agreement between the CCGs and the Trust. To facilitate and monitor the switching programme a new Band 7 IBD Biological nurse, a Band 7 IBD Biological pharmacist, and an IBD administrator were recruited. All patients were informed by letter of the planned switch and the rationale for it. A variety of clinical and biological markers were also recorded at each visit along with PROM data. Results: To date since the start of the project on 16 th September 2015 88 patients have been treated with biosimilar infliximab. 78 (63 CD/15 UC) patients on maintenance treatment with Remicade were switched to CT-P13 with unchanged efficacy and safety (the detailed results are the basis of a separate abstract); a further 10 patients received induction therapy (7 CD/3 UC). 3/88 patients requested further clarification from the IBD team with all patients subsequently agreeing to the switch. All patients were seen by either the IBD pharmacist or IBD specialist nurse and stated they felt well informed. Over the first six months the programme has generated total cost savings of £232, 576.52 with projected year savings of £540, 000. Staff costs totalled £90, 000. PROM data from the cohort revealed very high satisfaction with treatment with a mean score of 7.3 (Range 3–10) for overall disease control. Patient feedback was universally positive. Conclusion: The introduction of biosimilar infliximab can be achieved through a closely managed programme with very significant cost savings to the local health economy. Engaged conversations between primary and secondary care facilitate realising these savings allowing investment in the local IBD service with direct impact on patient care. Patients were overwhelmingly supportive of the project. Wider uptake in the UK would result in considerable cost savings to the NHS. Disclosure of Interest: None Declared